Sporadic intra-abdominal desmoid tumor - Santiago, Pablo; Cedrés, Adriana; Ferreira, Carlos; Yapur, Mónica (Cirugía del Uruguay, 2004)
A 44-year old patient consulted about an intra abdominal tumorous condition, which was found to be a desmoid tumor. There follows a description of the procedure in volved in its diagnosis and subsequent therapy. There are severa/ interesting elements to be derived from both bibliography and analysis of this case. In the first place, it is considerabley difficult to establish a differential diagnosis whit GISTs, it being necessary to resort to inmuno-histochemistry. lntra abdominal desmoids only correspond to 10% of al/ desmoids. On the other hand and given their rare occurrence there is little evidente as to the correct therapy to be applied.